Direct measurement of active thiol metabolite levels of clopidogrel in human plasma using tris(2‐carboxyethyl)phosphine as a reducing agent by LC–MS/MS. Issue 14 (21st June 2013) - Park, Jung Bae; Bae, Soo Hyeon; Jang, Su‐Min; Noh, Won Jun; Hong, Jang‐Hee; Yoon, Kee Dong; Kang, Han Chang; Bae, Soo Kyung
<x xml:space="preserve">Abstract</x> A simple, robust, and rapid LC–MS/MS method has been developed and validated for the simultaneous quantitation of clopidogrel and its active metabolite (AM) in human plasma. Tris(2‐carboxyethyl)phosphine (TCEP) was used as a reducing agent to detect the AM as a disulfide‐bonded complex with plasma proteins. Mixtures of TCEP and human plasma were deproteinized with acetonitrile containing 10 ng/mL of clopidogrel‐d4 as an internal standard (IS). The mixtures were separated on a C18 RP column with an isocratic mobile phase consisting of 0.1% formic acid in acetonitrile and water (90:10, v/v) at a flow rate of 0.3 mL/min. Detection and quantification were performed using ESI‐MS. The detector was operated in selected reaction‐monitoring mode at m/z 322.0→211.9 for clopidogrel, m/z 356.1→155.2 for the AM, and m/z 326.0→216.0 for the IS. The linear dynamic range for clopidogrel and its AM were 0.05–20 and 0.5–200 ng/mL, respectively, with correlation coefficients (r) greater than 0.9976. Precision, both intra‐ and interday, was less than 8.26% with an accuracy of 87.6–106%. The validated method was successfully applied to simultaneously analyze clinical samples for clopidogrel and its AM.